2013
DOI: 10.1007/s40145-013-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Progress on rare-earth doped ZnO-based varistor materials

Abstract: Rare-earth (RE) doping can greatly enhance the voltage gradient of ZnO-based varistors, and their nonlinear coefficient, leakage current, energy absorption capability, through-current capability and residual voltage can also be improved to certain extent. In this review, the progress on RE-doped ZnO-based varistor materials in recent years was summarized. The mechanism of RE doping on the electrical performance of ZnO varistors was analyzed. The issues in exploring new ZnO-based varistor materials by RE doping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The leakage current of the samples presented an opposite trend to that of nonlinear coefficient with ZrO 2 doping, and the varistors with 1 mol% ZrO 2 presented the lowest leakage current, 110  μ A/cm 2 , which is completely consistent with classic theory on their relationship [18]. Thus, it can be concluded that the optimum doping amount of ZrO 2 in the proposed SnO 2 -Ta 2 O 5 -ZnO-based ceramic varistor system was 1 mol%.…”
Section: Resultssupporting
confidence: 74%
“…The leakage current of the samples presented an opposite trend to that of nonlinear coefficient with ZrO 2 doping, and the varistors with 1 mol% ZrO 2 presented the lowest leakage current, 110  μ A/cm 2 , which is completely consistent with classic theory on their relationship [18]. Thus, it can be concluded that the optimum doping amount of ZrO 2 in the proposed SnO 2 -Ta 2 O 5 -ZnO-based ceramic varistor system was 1 mol%.…”
Section: Resultssupporting
confidence: 74%
“…With the increase of hot-dipping temperature, the leakage current of the samples shows a trend against the nonlinear coefficient. The high nonlinear coefficient for a varistor would lead to low leakage current because of the formation of a relatively high tunnel current, while the low nonlinear coefficient would result in high leakage current due to the formation of higher thermal excitation radio current25.…”
Section: Varistor Propertiesmentioning
confidence: 99%
“…1,2 Doping ZnO with rare earth (RE 3þ ) ions enables further electrical, optical, and magnetic applications due to the unique character of partially filled 4f shells. [3][4][5][6] For example, Yang et al 4 reported a light-emitting diode prototype based on RE-doped ZnO, capable of emitting across all wavelengths in the entire visible region. In addition, Gddoped/implanted ZnO exhibited room temperature (RT) ferromagnetic behavior that has been attributed to defect/impurity bands mediated by Gd dopants.…”
Section: Introductionmentioning
confidence: 99%